LITERATURE STUDY ON THE SCREENING OF Al-MOFs POROUS MATERIAL FOR DIMETHYL ETHER (DME) GAS PURIFICATION - Ahmad Syarwani; Yuniar Ponco Prananto (JURNAL INTEGRASI PROSES, 2023)
Renewable dimethyl ether (DME) gas is expected to replace LPG due to the high demand for domestic fuel gas and the shortage of LPG supply. DME properties are closely identical to that of LPG. DME gas can be produced directly and indirectly from various sources, including coal, natural gas, and other readily available biomass. The synthetic DME gas produces by-product gases, mainly CO2. Thus, purification of DME is needed. Al-MOF is proposed to be one of many candidates for CO2 gas absorption. A literature review was conducted in this study to screen some potential Al-MOF based on scientific peer-reviewed articles published in the last decade. The data were gathered by developing research questions using PICO(S) analysis. Particularly, this study highlights the effect of ligands on pore sizes, the effect of the amine group on absorption capacity, and the thermal stability of Al-MOF. This preliminary study finds several potential Al-MOFs suitable for the task. Based on this study, the NH2-MIL-53(Al) and NH2-MIL-101(Al) are highlighted as having the potency to be used in the DME purification process. However, further studies, including evidence-based gas separation experiments, are compulsory and need to be performed before this Al-MOF is applied to the DME purification process on a bigger scale.